Blow-up of solutions to a parabolic system with nonlocal source. Issue 5 (4th April 2018) - Dong, Zhihua; Zhou, Jun
Abstract : This paper deals with a parabolic system with different diffusion coefficients and coupled nonlocal sources, subject to homogeneous Dirichlet boundary conditions. The conditions on global existence, simultaneous or non-simultaneous blow-up, blow-up set, uniform blow-up profiles and boundary layer are got using comparison principle and asymptotic analysis methods.